A deep-space camera that can spot a volcano's puffs. (1st November 2018) - Unknown
Ash clouds from eruptions large and small are detected by a ﻿climate satellite's imaging instrument. Ash clouds from eruptions large and small are detected by a ﻿climate satellite's imaging instrument.